To determine if the equation represents a direct variation, we need to check if it can be written in the form y = kx, where k is the constant of variation.
Let's rearrange the equation to isolate y:
6y = 5x - 1
Divide both sides by 6:
y = (5x - 1)/6
We can see that the equation cannot be written in the form y = kx. Therefore, it does not represent a direct variation.
Determine whether the equation represents a direct variation. If it does, find the constant of variation.
6y = 5x - 1
7 answers
Question content area top
Part 1
Suppose y varies directly with x. Write a direct variation equation that relates x and y. Then find the value of y when x = 18.
y = 7 when x = 6
Part 1
Suppose y varies directly with x. Write a direct variation equation that relates x and y. Then find the value of y when x = 18.
y = 7 when x = 6
To write a direct variation equation, we use the form y = kx, where k is the constant of variation.
Given that y = 7 when x = 6, we can substitute these values into the equation to solve for k:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 7 * 3
y = 21
Therefore, when x = 18, y = 21.
Given that y = 7 when x = 6, we can substitute these values into the equation to solve for k:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 7 * 3
y = 21
Therefore, when x = 18, y = 21.
you sure?
Apologies for the mistake in my previous response. Let's correct it:
To write a direct variation equation, we use the form y = kx, where k is the constant of variation.
Given that y = 7 when x = 6, we can substitute these values into the equation to find k:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 21
Therefore, when x = 18, y = 21.
To write a direct variation equation, we use the form y = kx, where k is the constant of variation.
Given that y = 7 when x = 6, we can substitute these values into the equation to find k:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 21
Therefore, when x = 18, y = 21.
that was incorrect
Apologies for the confusion. Let's correct it:
Given that y varies directly with x, we can write the direct variation equation as y = kx, where k is the constant of variation.
To find the value of k, we can substitute the given values into the equation:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 21
Therefore, when x = 18, y = 21.
Given that y varies directly with x, we can write the direct variation equation as y = kx, where k is the constant of variation.
To find the value of k, we can substitute the given values into the equation:
7 = k * 6
Divide both sides by 6:
k = 7/6
Now that we have the value of k, we can write the direct variation equation:
y = (7/6)x
To find the value of y when x = 18, we substitute this value into the equation:
y = (7/6) * 18
y = 21
Therefore, when x = 18, y = 21.